Inventarisasi Mezofauna di Daerah Reklamasi PT. Freeport Indonesia, Timika–Papua - Sonya Wamafma; Pratita Puradjatmika (Jurnal Biologi Papua, 2009)
This study was conducted to identify the mesofauna inhabiting the reclamation area (Grasberg) and the natural succession (Ertsberg), to observe the development of mesofauna and to know the species compotition in the given area. Research method was pitfall trap that set up in reclamation area, natural succession and in control area. The result revealed that mesofauna in reclamation area were dominated by the family Isotomidae and Neelidae (Ordo Collembola) with the relative dominancy value 23,90% and 24,37% respectively, the presence or relative frequency 9,23% and 9,23%, and relative density value 23,90% dan 24,37% individuals/m³. Mesofauna in succession area Ertsberg were dominated by the family Neelidae (Ordo Collembola) with the relative dominancy value 31,85%, the presence or relative frequency 5,41% and relative dencity value 31,85% individual/m³. The dominant mesofauna in control area was famili Neelidae (Ordo Collembola) with the relative dominancy value 22,5%, the presence or relative frequency 4,17%, and the relative density value was 22,5% individual/m³. Phylum Arthropoda dominated the whole study area with the total individual 2089, whereas Phylum Annelida consisted of 33 individuals. The highest species composition was found in Menado Leach Pad (509 individuals) followed by Jayapura Crusher (322 individuals) and Ertsberg Lower (301 individuals). Species composition of mesofauna in the study area was generally grouped into two phyilum; Arthropoda and Annelida which consisted of 4 classes, 13 ordo, 38 families and 2122 individuals. Environmental recovery undertaken by the Freeport Company through reclamation and natural succession was successfully done as indicated by the occurrence of various vegetation and mesofauna that interact each other.Key words: Mesofauna, reclamation area Grasberg, natural succession Erstberg, Freeport Company, Timika.